Salmonella enterica serovar Choleraesuis vector delivering SaoA antigen confers protection against Streptococcus suis serotypes 2 and 7 in mice and pigs - Li, Yu-an; Ji, Zhenying; Wang, Xiaobo; Wang, Shifeng; Shi, Huoying (Veterinary research (Paris), 2017)
Streptococcus suis is one of the major pathogens that cause economic losses in the swine industry worldwide. However, current bacterins only provide limited prophylactic protection in the field. An ideal vaccine against S. suis should protect pigs against the clinical diseases caused by multiple serotypes, or at least protect against the dominant serotype in a given geographic region. A new recombinant Salmonella enterica serotype Choleraesuis vaccine vector, rSC0011, that is based on the regulated delayed attenuation system and regulated delayed antigen synthesis system, was developed recently. In this study, an improved recombinant attenuated Salmonella Choleraesuis vector, rSC0016, was developed by incorporating a sopB mutation to ensure adequate safety and maximal immunogenicity. In the spleens of mice, rSC0016 colonized less than rSC0011. rSC0016 and rSC0011 colonized similarly in Peyer's patches of mice. The recombinant vaccine rSC0016(pS-SaoA) induced stronger cellular, humoral, and mucosal immune responses in mice and swine against SaoA, a conserved surface protein that is present in many S. suis serotypes, than did rSC0011(pS-SaoA) without sopB or rSC0018(pS-SaoA), which is an avirulent, chemically attenuated vaccine strain. rSC0016(pS-SaoA) provided 100% protection against S. suis serotype 2 in mice and pigs, and full cross-protection against SS7 in pigs. This new vaccine vector provides a foundation for the development of a universal vaccine against multiple serotypes of S. suis in pigs.